2014
DOI: 10.3109/14764172.2014.949274
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of effects of platelet-rich plasma on human facial skin

Abstract: PRP application could be considered as an effective procedure for facial skin rejuvenation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 19 publications
1
62
0
3
Order By: Relevance
“…They reported that PRP combined with fractional laser increased subject satisfaction and skin elasticity, the amount of collagen, and the number of fibroblasts. Yuksel et al11 investigated the effect of PRP on the human facial skin. They applied to PRP with dermaroller and intradermal injections.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that PRP combined with fractional laser increased subject satisfaction and skin elasticity, the amount of collagen, and the number of fibroblasts. Yuksel et al11 investigated the effect of PRP on the human facial skin. They applied to PRP with dermaroller and intradermal injections.…”
Section: Discussionmentioning
confidence: 99%
“…P-PRP was applied to the forehead, malar area, and jaw by a dermaroller, as well as injected using a 27-gage needle into the wrinkles of crow's feet. They found there was a statistically significant difference between the general appearance, skin firmness-sagging and wrinkle state before and after the applications [46]. Mehryan et al assessed the effect of P-PRP on infraorbital dark circles and crow's feet.…”
Section: Human Trialsmentioning
confidence: 97%
“…Pancar ve ark. 'nın (11) yaptığı çalışmada, 10 sağlıklı gönüllü-ye 2 hafta ara ile 3 kez yüz derisine PRP uygulaması yapılmış ve genel görünüm, cilt sıkılığı ve kırışıklık durumu yönünden PRP grubunda anlamlı farklılık gözlenmiştir. Margolis ve ark.…”
Section: Platelet-zengin Plazma Ile Yapılan Insan Ve Deneysel Havyan unclassified